PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM MEMASUKI ERA DIGITAL TANTANGAN DAN SOLUSI MENUJU TRANSAKSI ELEKTRONIK YANG AMAN, NYAMAN DAN TERPERCAYA - Pratama, Bisma Putra; Sembiring, Susanti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The development of information and communication technology has had a significant impact on the world of trade, changing conventional transactions into electronic transactions that are more efficient and practical. Although electronic transactions offer many conveniences such as wide access and fast processing, consumers are faced with high risks such as online fraud, identity theft and misuse of personal data. In Indonesia, consumer protection efforts have been regulated in Law Number 8 of 1999 concerning Consumer Protection. However, this regulation needs to be adapted to the dynamics of the digital era which continues to develop. This research aims to examine legal protection for consumers in the digital era as well as effective solutions to create safe, comfortable and reliable electronic transactions. The research method used is normative juridical with a statutory and conceptual approach. The research results show that legal protection of consumers in the digital era requires strict regulations, continuous education, and the use of security technology. Proposed solutions include strengthening regulations, increasing digital literacy, using security technologies such as encryption and two-factor authentication, as well as providing efficient dispute resolution mechanisms. Collaboration between the government, business actors and the community is also considered important to create a safer and more reliable electronic transaction ecosystem. It is hoped that the implementation of this solution can provide better protection for consumers and encourage sustainable digital economic growth in Indonesia.Keywords: Legal Protection, Consumers, Digital Era, Electronic Transactions, Cyber Security